The role of spatial abilities and age in performance in an auditory computer navigation task. - Pak, Richard; Czaja, Sara J.; Sharit, Joseph; Rogers, Wendy A.; Fisk, Arthur D. (Computers in Human Behavior, 2008)
Age-related differences in spatial ability have been suggested as a mediator of age-related differences in computer-based task performance. However, the vast majority of tasks studied have primarily used a visual display (e.g., graphical user interfaces). In the current study, the relationship between spatial ability and performance in a non-visual computer-based navigation task was examined in a sample of 196 participants ranging in age from 18 to 91. Participants called into a simulated interactive voice response system and carried out a variety of transactions. They also completed measures of attention, working memory, and spatial abilities. The results showed that age-related differences in spatial ability predicted a significant amount of variance in performance in the non-visual computer task, even after controlling for other abilities. Understanding the abilities that influence performance with technology may provide insight into the source of age-related performance differences in the successful use of technology. Copyright (c) 2008 Elsevier Ltd.